(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the modern innovative approaches applied in teaching the Uzbek language, their effectiveness, and their role in developing students’ language skills. It also highlights the advantages of using information and communication technologies, interactive methods, and communicative approaches in the educational process.